A study of psychological empowerment and its impact on job engagement of visually impaired employees during COVID-19 Lockdown (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This scientific investigation attempt’s by  differently-abled employees began as a quest  into their own psychological empowerment. The authors attempted to study the relationship  between psychological empowerment of  differently-abled ( visually impaired) employees  and their work engagement across different  sectors in India during CIVID19 lockdown. The  research design employed both quantitative and  qualitative data through surveys and interviews.  Results indicate a significant relationship  between psychological empowerment and work  engagement. The study has implications for  human resource professionals, managers and  researchers.
Keywords: empowerment; interviews; scientific